Examination of Arterial Stiffness and Neurodynamics of Middle-Aged Individuals: A Pilot Study. Issue 4 (October 2017) - Gugliotti, Mark; Ingenito, Teresa; Douris, Peter; Jung, Min-Kyung; Asaro, Alessandro; Epifania, Jillian; Garrick, Robert; Kartsev, Gleb; Lin, Yiyu; Mathew, Brian; Paul, Anika
Abstract : Purpose: Increases in arterial stiffness can result in higher pulse wave velocity (PWV) of the arterial blood leading to arterial vascular disease. Studies have shown high PWV is correlated to poor trunk and hamstring flexibility. Poor trunk and hamstring flexibility has additionally been correlated to the presence of neuropathodynamics (NPD) within the peripheral nervous system. Although the coexistence of poor hamstring flexibility and NPD is clear, a paucity of data exists to suggest any relationship between NPD and increased arterial stiffness. We hypothesized a significant relationship would exist between NPD and increased arterial stiffness. Methods: This was a cross-sectional study. The PWV, blood pressure, range of motion, hamstring flexibility, and neurodynamic response to a straight leg raise was measured in 47 middle-aged adults. Correlation and regression analyses were performed to examine relationships among PWV, age, blood pressure, sex, fitness level, hamstring flexibility, and neurodynamic response. Results: The presence of NPD was found not to be a significant predictor of PWV. Only systolic blood pressure (SBP) ( P = .003) and age ( P = .012) was found to be significant predictor variables for PWV. Conclusions: The results of this study show no significant relationship between NPD and arterial stiffness. Our findings do, however, indicate that SBP and age should be considered valid predictor variables of underlying arterial vascular disease.